Composted Cattle Manure Increases Microbial Activity and Soil Fertility More Than Composted Swine Manure in a Submerged Rice Paddy - Das, Suvendu; Jeong, Seung Tak; Das, Subhasis; Kim, Pil Joo (Frontiers in Microbiology, 2017)
The livestock waste composts with minimum inorganic fertilizer as a soil amendment in low-input intensive farming are a feasible agricultural practice to improve soil fertility and productivity and to mitigate soil degradation. The key benefits of the practice rely on the activities of soil microorganisms. However, the role of different livestock composts (composted cattle manure vs. composted swine manure) on soil microbes, their activities and the overall impact on soil fertility and productivity in a flooded paddy remains elusive. This study compared the effectiveness of composted cattle manure (CCM) and composted swine manure (CSM) amendment on bacterial communities, activities, nutrient availability and crop yield in a flooded rice cropping system. We used deep 16S amplicon sequencing and soil enzyme activities to decipher bacterial communities and activities, respectively. Both CCM and CSM amendment significantly increased soil pH, nutrient availability (C, N, and P), microbial biomass, soil enzyme activities indicative for C and N cycles, aboveground plant biomass and grain yield. And the increase in above-mentioned parameters was more prominent in the CCM treatment compared to the CSM treatment. The CCM amendment increased species richness and stimulated copiotrophic microbial groups (Alphaproteobacteria, Betaproteobacteria and Firmicutes) which are often involved in degradation of complex organic compounds. Moreover, some dominant species (e.g., Azospirillum zeae, Azospirillum halopraeferens, Azospirillum rugosum, Clostridium alkalicellulosi, Clostridium caenicola, Clostridium termitidis, Clostridium cellulolyticum, Magnetospirillum magnetotacticum, Pleomorphomonas oryzae, Variovorax boronicumulans, Pseudomonas xanthomarina, Pseudomonas stutzeri, and Bacillus niacini) which have a key role in plant growth promotion and/or lignocellulose degradation were enhanced under CCM treatment compared to CSM treatment. Multivariate analysis revealed that soil pH and available C and N were the major, while TOC, TN, and available P were the minor drivers of variation in bacterial communities. Together, it could be suggested that CCM amendment is better than CSM amendment to improve soil fertility and crop yield in a submerged rice cropping system.